The Role of Heat Transfer Limitations in Polymer Pyrolysis at the Microscale - Richter, Franz; Rein, Guillermo (Frontiers in Mechanical Engineering, 2018)
Thermal degradation of synthetic and natural polymers is an important process in many fields of engineering such as fire safety, thermal recycling, and biomass power generation. The kinetics of thermal degradation is usually studied by thermogravimetric analysis (TGA), which is based on measuring the mass loss rate of a microscale sample and the temperature of the surrounding fluid during controlled heating. The literature is rich in TGA measurements, which are commonly assumed to be governed solely by kinetics. Heat and mass transfer effects, however, can occur when the sample is insufficiently small in size. Only a few studies quantify a threshold for this maximum size. These thresholds vary due to different input parameters and formulations of the used model. Here, we aim to systematically analyse the role of heat transfer in TGA experiments, quantify the uncertainty of current models, and provide a novel threshold for maximum sample size. We focused on the natural polymer cellulose, a surrogate for biomass, and split the problem into heat transfer within the sample (intraparticle) and between the sample and the fluid (interparticle). Using dimensional analysis we derived two upper bound thresholds for the initial sample mass as a function of heating rate above these thresholds heat transfer effects are significant. One threshold is calculated based on interparticle heat transfer and depends on flow conditions, material and fluid properties. The other is calculated based on intraparticle heat transfer and only depends on material properties. Both thresholds were validated with experiments and previous studies from the literature. Comparing both thresholds shows that the maximum sample mass in a TGA is always limited by interparticle heat transfer. These results enable the selection of appropriate samples masses and heating condition in TGA experiments, which in turn will lead to a better understanding of the pyrolysis chemistry of polymers.